Trivalent inactivated influenza vaccine (IIV3) during pregnancy and six-month infant development. Issue 10 (28th February 2020) - Avalos, Lyndsay A.; Ferber, Jeannette; Zerbo, Ousseny; Naleway, Allison L.; Bulkley, Joanna; Thompson, Mark; Cragan, Janet; Williams, Jennifer; Odouli, Roxana; Kauffman, Tia L.; Ball, Sarah; Shifflett, Pat; et al.
Abstract: Objective: Despite recommendations by professional organizations that all pregnant women receive inactivated influenza vaccine, safety concerns remain a barrier. Our objective was to assess the effect of trivalent influenza vaccines (IIV3) during pregnancy on parent report 6-month infant development. Methods: We conducted a multi-site prospective birth cohort study during the 2010–2011 influenza season and followed pregnant women and their newborns through 6 months of age. Information on IIV3 during pregnancy was ascertained from the EHR and self-report. The Ages and Stages Questionnaire-3 (ASQ-3) was completed by the mother to assess 6-month infant neurodevelopment in five domains (communication, gross motor, fine motor, problem-solving, and personal adaptive skills). Scores for each domain above the cut-off point indicating typical development were categorized as "on schedule" while scores in the zones indicating the need for either monitoring or further assessment were categorized as "not on schedule". Multivariable logistic regression was conducted. Results: Of the 1225 infant-mother pairs, 65% received IIV3 during pregnancy. In bivariate analysis, infants of women who received IIV3 during pregnancy were moderately-less likely to need monitoring or further assessment in the personal social domain compared with infants of unvaccinated women (10.0% vs. 14.1%, p = 0.033; crude OR (cOR): 0.68(95%CI:0.48, 0.97)). However, after controlling for potential confounders, the findings were no longer statistically significant (aOR:0.72, 95%CI: 0.49, 1.06, p = 0.46). No significant unadjusted or adjusted associations emerged in any other ASQ-3 domain. Conclusion: There was no significant association between IIV3 exposure during pregnancy and 6-month infant development. Studies of IIV3 during pregnancy to assess longer-term developmental outcomes are indicated.